Implementasi Standar Operasional Prosedur (SOP) Pemeliharaan Sarana Prasarana untuk Meningkatkan Efisiensi dan Efektivitas Kinerja Pegawai di DP3AKKB - Natasya Revita; Eli Apud Saepudin; Rizki Amilia (Universitas Serambi Mekkah, 2026)
This study is motivated by the importance of implementing Standard Operating Procedures (SOPs) for infrastructure maintenance to ensure organizational asset sustainability while improving employee efficiency and effectiveness at the Office of Women's Empowerment, Child Protection, Population Control, and Family Planning (DP3AKKB). The primary issues include the suboptimal implementation of SOPs, limited supervision, and inconsistent maintenance practices that affect service quality and employee productivity. This study aims to analyze the implementation of infrastructure maintenance SOPs and identify the factors influencing their effectiveness. A descriptive qualitative approach was employed using observation, in-depth interviews, documentation, and literature review as data collection techniques. Data were analyzed through data reduction, data display, and conclusion drawing, with source and technique triangulation used to ensure data validity. The findings indicate that the SOP implementation has generally been carried out in accordance with established procedures; however, several challenges remain, including limited maintenance budgets, low compliance with maintenance schedules, and insufficient monitoring and evaluation. Nevertheless, the implementation of SOPs has positively contributed to improving workplace readiness, optimizing the utilization of facilities, accelerating work completion, and enhancing employee performance effectiveness. The study concludes that optimizing SOP implementation through strengthened supervision, improved employee competencies, and regular evaluation can significantly enhance infrastructure management quality and support the achievement of organizational objectives.